(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Reports are available indicating that leaded gasoline is still being made available in some parts of the world. Moreover it is also known that the crude from which petroleum products are obtained is rich in heavy metals. This means heavy metal toxicity from petrol contact is a possibility. The aim of this study is to assess selected heavy metal levels in teenagers who are currently and formerly employed as GSA. Materials and Methods: The study population consisted of teenagers divided into 3 groups. GROUP I was made up of 30 male subjects that are currently employed as GSA with less than 6 months work history; GROUP II composed of 34 male teenagers with work history in gas station not less than 20 months; GROUP III consisted of 22 male teenagers who were former attendants; the control group consisted of 35 participants, with no history of occupational exposure to fuel, or heavy metals. Information was obtained through questionnaire on demography, life-style and clinical symptoms of gasoline exposure. Serum heavy metal levels were estimated using atomic absorption spectrometry. Student’s t test and analysis of variance were employed to determine the level of significant difference. P < 0.05 was considered significant. Results and Discussion: The serum levels of lead, arsenic, nickel, cadmium, and aluminium of GSA in GROUPS I and II were significantly higher compared with control. On the other hand, there were significant increases in levels of lead and cadmium in GROUP III compared with control. Additionally, majority of test subjects in GROUPS I and II identified headache and fatigue as symptoms associated with workplace. Teenage GSA are prone to heavy metal toxicity and discontinuing contact with gas station environment did not resolve this occupational hazard. Conclusion: Gonadotoxic effect of some of these elements on these categories of subjects who are within reproductive stage is possible. Therefore appropriate measure should be taken to address it. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.224-229